2017
DOI: 10.1021/acs.biomac.7b00067
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Xylan Side-Chain Substitutions on Xylan–Cellulose Interactions and Implications for Thermal Pretreatment of Cellulosic Biomass

Abstract: Lignocellulosic biomass is mainly constituted by cellulose, hemicellulose, and lignin and represents an important resource for the sustainable production of biofuels and green chemistry materials. Xylans, a common hemicellulose, interact with cellulose and often exhibit various side chain substitutions including acetate, (4-O-methyl) glucuronic acid, and arabinose. Recent studies have shown that the distribution of xylan substitutions is not random, but follows patterns that are dependent on the plant taxonomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
51
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 51 publications
(95 reference statements)
7
51
0
1
Order By: Relevance
“…Although the conformation of the backbone is the same on both surfaces considered here, the hydrophobic surfaces seem to stabilize the conformation of the side groups docked on them compared with the hydrophilic surfaces. This conclusion is in agreement with previous observations reporting the migration of an AGX chain from the hydrophilic surface to the hydrophobic surface of cellulose upon thermal treatment at 160°C using MD simulations (Pereira et al, 2017).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Although the conformation of the backbone is the same on both surfaces considered here, the hydrophobic surfaces seem to stabilize the conformation of the side groups docked on them compared with the hydrophilic surfaces. This conclusion is in agreement with previous observations reporting the migration of an AGX chain from the hydrophilic surface to the hydrophobic surface of cellulose upon thermal treatment at 160°C using MD simulations (Pereira et al, 2017).…”
Section: Discussionsupporting
confidence: 94%
“…It is noteworthy that the latter two were positioned with their side groups pointing away from the surface, whereas XXXU m U m X, which exhibited the strongest interaction, has one side group pointing directly to the cellulose. This is in agreement with a recent study that showed that a-(1→2)-linked substitutions improve the interaction between xylan and cellulose (Pereira et al, 2017). These results also clearly show that the interaction with the hydrophobic (200) surface is stronger compared with the hydrophilic (1-10) one.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…This depiction is a synthesis based on the most recent results from AFM, FESEM, solid-state NMR, and mechanics. the hydrophilic faces of cellulose (Simmons et al, 2016;Grantham et al, 2017;Pereira et al, 2017). Primary cell walls generally contain only small amounts of xylan, e.g.…”
Section: Cell Wall Models Need Further Refinement and Testingmentioning
confidence: 99%
“…37 Both the empirical and computational analyses confirmed that high molecular weight and unsubstituted xylans show highest affinity to cellulose; 35−38 molecular dynamics simulations also predict impacts of substituent distribution on the stability of cellulose associations. 38,39 In the present study, two different arabinofuranosidases were used to selectively remove distinct α-L-Araf substituents from wheat arabinoxylan (WAX) prior to graft copolymerization with glycidyl methacrylate (GMA). GMA was selected as the monomer for the grafting experiments as it was previously shown to react well with polysaccharides, including hemicelluloses, 18 and because the epoxy groups introduced through GMA grafting creates sites that can be further chemically modified depending on the end use.…”
Section: ■ Introductionmentioning
confidence: 99%